2018
DOI: 10.1007/s11837-018-3056-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Liquid–Liquid Mass Transfer and the Influence of Mixing in Gas-Stirred Ladles

Abstract: Ladle refining plays a key role in the steelmaking process. During the refining, a bubbly gas stream is used for mixing and to enhance the rate of removal of impurities from the molten steel. A numerical model has been developed to understand mass transfer and mixing behavior in a three-phase gas-stirred ladle. A two-resistance approach was used for the liquid-liquid mass transfer, while the mass transfer coefficient was determined using the Small Eddy theory. The model was validated with experimental data, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Nevertheless, the rising bubbles form a turbulent bubble plume, and the resulting slag eye causes the reoxidation of liquid steel. Intense interactions occur between the slag and molten steel because the overlying slag is pushed to the side . It is widely known that the bubble size and its motion affect momentum, heat, and mass transfer in gas–liquid bubble flow .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the rising bubbles form a turbulent bubble plume, and the resulting slag eye causes the reoxidation of liquid steel. Intense interactions occur between the slag and molten steel because the overlying slag is pushed to the side . It is widely known that the bubble size and its motion affect momentum, heat, and mass transfer in gas–liquid bubble flow .…”
Section: Introductionmentioning
confidence: 99%
“…Mixing time is a parameter that measures the mixing efficiency of the primary phase (liquid steel) in a bath. Mathematically, it is defined as the time at which there is a chemical homogeneity of 95% in the steel [5]. Mixing time helps to quantify the degree of agitation needed to homogenize the liquid contents after a step change in the composition inside a ladle.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if mixing time is of interest, a dynamic treatment for the free surface is required. Recently, Hoang et al [15] studied mixing time in ladle to observe its influence on mass transfer. They observed that mixing is accomplished in a much shorter time than interphase mass transfer, specifically by two orders of magnitude, which indicated that mass transfer is the rate-limiting step.…”
Section: Introductionmentioning
confidence: 99%